The effects of working and living conditions of physicians on burnout level and sleep quality - Hacimusalar, Yunus; Misir, Emre; Civan Kahve, Aybeniz; Demir Hacimusalar, Goknur; Guclu, Muhammed Alperen; Karaaslan, Ozgul (La Medicina del Lavoro, 2021)
Background: Burnout is a multidimensional syndrome associated with intense working conditions and negative psychosocial factors in physicians. The purpose of this study is to investigate the effects of living and working conditions of physicians on burnout level and sleep quality in Turkey. Methods: In this internet-based questionnaire study, 1053 physicians [General Practitioners (n=233); Basic Medical Sciences (n=26); Internal Medical Sciences (n=530), and Surgery Sciences (n=264)] were included in the study, filling the forms consisting of study conditions, Maslach Burnout Inventory (MBI) and the Pittsburgh Sleep Quality Index (PSQI) questions. Results: Negative occupational factors such as physicians having a night shift, high number of patients who are cared for daily, short examination period, low financial gain, exposure to violence, and mobbing were associated with poor sleep quality and burnout. Factors such as being subjected to violence, mobbing, and age are predictive of increasing burnout in women. Working on night shifts or being on-call were associated with all aspects of burnout. The proportion of those with poor sleep quality was significantly higher in those working night shifts (74.6%) than those working daytime shifts (67.2%) and those who were exposed to violence (75.1%) compared to those who were not exposed to violence (43.2%) (p=0.013, p